PEMENUHAN HAK NARAPIDANA PEREMPUAN HAMIL DAN MENYUSUI DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIA SEMARANG - Ula, Rifa Tafa’ul; Ananda, FaridFarid Rizqi (jurnal.unprimdn.ac.id, 2023)
The fulfillment of rights for female prisoners at the Women's Correctional Institution Class IIA Semarang experiences several difficulties. Female prisoners have natures that men, such as pregnancy, childbirth, breastfeeding, and menstruation, do not own. In October 2023, there were 2 pregnant female prisoners in Semarang Women's Correctional Facility. The purpose of this research is to find out how the implementation of the Correctional Act in fulfilling the rights of prisoners, especially pregnant women. The method used in this research is an empirical juridical method; primary data is taken from the law, while secondary data is obtained from interviews with prison officers. The result of the research is that the fulfillment of the rights of female prisoners, especially pregnant and breastfeeding women, has been well implemented by statutory regulations, such as a complete clinic with doctors and nurses, extra feeding, immunization, and referral to the hospital when approaching HPL. However, Semarang Women's Prison has several obstacles, such as the need for more facilities, minimal human resources, and a small budget from the government.